NILAI EKONOMI TOTAL SUMBERDAYA BAMBU (Bambuseae sp.) DI KECAMATAN SAJIRA, KABUPATEN LEBAK, BANTEN - Mohamad Iqbal; Eka Intan Kumala Putri; Bahruni Bahruni (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
The abundant availability of bamboos in Indonesia has prompted their possible uses as substitute for conventional raw materials (i.e. woods) which nowadays tend to be dwindling. Bamboo produces a wide range of benefits both tangible and intangible which has not been calculated. The benefits of bamboo do not all have a market price, so that it is necessary to quantify the economic value of bamboo resources in monetary units. This research aims to quantify the total economic value (TEV) of bamboo resources in Sajira subregency as one of the main centers of bamboo area in Lebak Regency. Values of bamboo resources estimated are direct use value (the stumpage value of bamboo), indirect use values such as the value of carbon sequestration and erosion prevention value, and the option value of surat (Gigantochloa pseudoarundinacae). Research methods used are derived residual value approach, market prices, replacement cost method, and Contingent Valuation Method (CVM). Results showed that direct use values (stumpage value of bamboo) is IDR 35,126,575,400, carbon stock value is IDR 224,840,000, erosion prevention value is IDR 695,341,881 and the option value of surat is IDR 82,014,259.TEV of bamboo resources for 140 ha of bamboo stands is IDR 36,128,771,540.